Effect on Osteogenic Differentiation of Genetically Modified IL4 or PDGF-BB Over-Expressing and IL4-PDGF-BB Co-Over-Expressing Bone Marrow-Derived Mesenchymal Stromal Cells In Vitro - Masanori Tsubosaka (MDPI AG, 2021)
The use of genetically modified (GM) mesenchymal stromal cells (MSCs) and preconditioned MSCs (pMSCs) may provide further opportunities to improve the outcome of core decompression (CD) for the treatment of early-stage osteonecrosis of the femoral head (ONFH). GM interleukin-4 (IL4) over-expressing MSCs (IL4-MSCs), platelet-derived growth factor (PDGF)-BB over-expressing MSCs (PDGF-BB-MSCs), and IL4-PDGF-BB co-over-expressing MSCs (IL4-PDGF-BB-MSCs) and their respective pMSCs were used in this in vitro study and compared with respect to cell proliferation and osteogenic differentiation. IL4-MSCs, PDGF-BB-MSCs, IL4-PDGF-BB-MSCs, and each pMSC treatment significantly increased cell proliferation compared to the MSC group alone. The percentage of Alizarin red-stained area in the IL4-MSC and IL4-pMSC groups was significantly lower than in the MSC group. However, the percentage of Alizarin red-stained area in the PDGF-BB-MSC group was significantly higher than in the MSC and PDGF-BB-pMSC groups. The percentage of Alizarin red-stained area in the IL4-PDGF-BB-pMSC was significantly higher than in the IL4-PDGF-BB-MSC group. There were no significant differences in the percentage of Alizarin red-stained area between the MSC and IL4-PDGF-BB-pMSC groups. The use of PDGF-BB-MSCs or IL4-PDGF-BB-pMSCs increased cell proliferation. Furthermore, PDGF-BB-MSCs promoted osteogenic differentiation. The addition of GM MSCs may provide a useful supplementary cell-based therapy to CD for treatment of ONFH.